Measurement of a double spin asymmetry in the photoproduction of π−π−-mesons on deuterons; The European Physical Journal A; Vol. 54, iss. 10 - Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Lazarenko B. A. Boris Aleksandrovich; Loginov A. Yu. Aleksey Yurievich; Mishnev S. I. Svyatoslav Igorevich; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I. A. Igor Anatoljevich; Sadykov R. Sh. Rustam Shagitovic; Shestakov Yu. V. Yury Vladimirovich; Toporkov D. K. Dmitry Konstantinovich; Zevakov S. A. Sergey Aleksandrovich (2018, 2018)
Title screen